PEMBERDAYAAN PENGELOLAAN SAMPAH ORGANIK BERBASIS EKONOMI SIRKULAR MELALUI PRODUK KOMPOS PADA KOMUNITAS SENAM NUSANTARA (KSN) KOTA TANGERANG SELATAN - Agus Sudarsono; Abdul Khoir; Suhandi (Abdi Jurnal Publikasi, 2026)
This Community Service (PKM) activity aims to enhance public understanding and awareness regarding organic waste management through a circular economy approach. The activity was conducted on April 25–26, 2026, with the *Kelompok Senam Nusantara* (KSN) group in South Tangerang City, involving 30 participants. The methods employed included educational sessions, discussions, and Q&A sessions covering organic waste management, waste sorting, and the application of circular economy principles in daily life. The results indicate an increase in participants' understanding and awareness regarding the importance of sustainable waste management and the utilization of organic waste to create products of value. This activity is expected to foster behavioral changes within the community regarding environmental cleanliness and support the creation of a clean, healthy, and sustainable environment.